The Free Radical Scavenging Property of the Leaves, Branches, and Roots of Mansoa hirsuta DC: In Vitro Assessment, 3D Pharmacophore, and Molecular Docking Study - Alves, Patrícia e Silva; Preet, Gagan; Dias, Leandro; Oliveira, Maria; Silva, Rafael [UNESP]; Castro, Isione; Silva, Giovanna; Júnior, Joaquim; Lima, Nerilson; Silva, Dulce Helena [UNESP]; Andrade, Teresinha; Jaspars, Marcel; et al. (MDPI, 2022)
In this work, a metabolic profile of Mansoa hirsuta was investigated, and in vitro assays and theoretical approaches were carried out to evaluate its antioxidant potential. The phytochemical screening detected saponins, organic acids, phenols, tannins, flavonoids, and alkaloids in extracts of leaves, branches, and roots. Through LC-MS analysis, the triterpenes oleanolic acid (m/z 455 [M-H]−) and ursolic acid (m/z 455 [M-H]−) were identified as the main bioactive components. The extracts of the leaves, branches, and roots revealed moderate antioxidant potential in the DPPH test and all extracts were more active in the ABTS test. The leaf extracts showed better antioxidant capacity, displaying IC50 values of 43.5 ± 0.14, 63.6 ± 0.54, and 56.1 ± 0.05 µg mL−1 for DPPH, ABTS, and kinetics assays, respectively. The leaf extract showed higher total flavonoid content (TFC) (5.12 ± 1.02 mg QR/g), followed by branches (3.16 ± 0.88 QR/g) and roots (2.04 ± 0.52 QR/g/g). The extract of the branches exhibited higher total phenolic content (TPC) (1.07 ± 0.77 GAE/g), followed by leaves (0.58 ± 0.30 GAE/g) and roots (0.19 ± 0.47 GAE/g). Pharmacophore and molecular docking analysis were performed in order to better understand the potential mechanism of the antioxidant activity of its major metabolites.
Keywords: antioxidant; Mansoa hirsuta; molecular docking; oxidative stress; pharmacophore; triterpenes